PROMOTING COCOA EXPORT FOR TRANSFORMATIVE AND SUSTAINABLE AGRICULTURAL GROWTH IN NIGERIA - Ukpe, Udeme Henrietta; Onuigbo, Iheanyi (Applied Studies in Agribusiness and Commerce, 2025)
This study was carried out to assess whether cocoa export crop could serve as driver for transformative and sustainable agricultural growth in Nigeria. Data were collected from secondary sources. Vector Error correction, impulse response and variance decomposition were used as analytical tools. The results showed that the in the short run the coefficient of determination (R2) was 0.507 indicating that 50.7% of the variation in agricultural growth was explained by cocoa export, exchange rate, government expenditure and labour. There is a positive short run relationship and a negative long run relationship between cocoa export and agricultural growth. Labour exhibits an adverse effect in the short and long run on agricultural growth. Also, the result shows a short and long run positive relationship between exchange rate, government agricultural spending, and agricultural growth. Agricultural growth responded positively to a unit shock in Cocoa export and exchange rate in both the short run and long run. It was recommended that government should be proactive in its responsibilities by increasing budgetary allocation to agriculture and monitoring of its distribution, incentivize local investors and cocoa farmers, put in place viable export policy and appropriate exchange rate policy to stabilize the Nigerian economy. This will restore the place of Nigeria in the competitive cocoa market as well as increase agricultural growth.